Late Pleistocene Fauna of Lost Chicken Creek, Alaska - Porter, Lee (ARCTIC, 1988)
The fossil remains of one invertebrate and 16 vertebrate genera have been recovered from late Quaternary sediments of a large placer gold mine in east-central Alaska. Forty-six of 1055 fossils were recovered in situ from nine stratigraphic units at the Lost Chicken Creek Mine, Alaska. The fossils range in age from approximately 1400 yr BP (Alces alces) to greater than 50,400 yr BP (Equus [Asinus] lambei, Rangifer tarandus, Ovibovini cf. Symbos cavifrons, and Bison priscus). The assemblage includes an unusual occurrence of gallinaceous birds (Lagopus sp., ptarmigan), wolverine (Gulo gulo), the extinct American lion (Panthera leo atrox), collared lemmings (Dicrostonyx torquatus), and saiga antelope (Saiga tatarica). Sediments at Lost Chicken Creek consist of 37 vertical m of sandy silt, pebbly sand, gravel and peat of fluvial, colluvial and eolian origins. Four episodes of fluvial deposition have alternated sequentially throughout the late Wisconsinan with periods of eolian deposition and erosion. Solifluction has created a disturbed biostratigraphy at the site, yielding a fauna that must be considered a thanatocoenosis. The stratigraphy of Lost Chicken Creek is strikingly similar in major features to that of two coeval Beringian localities: Canyon Creek and Eva Creek, Alaska.Key words: Beringia, Pleistocene, fauna, ecology, mammals Mots clés: Béringie, pléistocène, faune, écologie, mammifères